Literature study on the implementation of data-based planning to improve education quality - Lutfiartha, Hansen; Wuryandini, Endang; Muhtarom, Muhtarom (Educenter : Jurnal Ilmiah Pendidikan, 2025)
The study aims to systematically synthesize various empirical research findings on the implementation of Data-Based Planning (PBD) in schools as an effort to improve the quality of education. An Integrative Literature Review approach was used in the study by analyzing five scientific articles. Articles published in 2024-2025 that were relevant to the topic of PBD and the use of Education Reports were used as research data sources. A thematic analysis was conducted on four main aspects, namely the role of Education Reports as an identification tool, DBP implementation strategies, obstacles and challenges, and their impact on quality improvement. The synthesis results show that Education Reports serve as a diagnostic and reflective instrument to objectively identify quality issues. Effective PBD implementation involves collaboration between teachers, principals, and stakeholders in integrating data into school program planning. The main challenges faced include low data literacy and a weak culture of reflection in schools. Nevertheless, the application of PBD has been proven to improve teacher professionalism, strengthen a culture of reflection, and encourage continuous improvement of the school quality management system.